A vilegiatura marítima e a urbanização em Tibau/RN - Batista, Joane Luiza Dantas Vieira (2013)
This research aims the analysis of the urbanization process that has taken place in the coastal city of Tibau/RN in the period comprising 1980-2012, due to the (re) production of space to consumption of leisure and recreation, through the so called practice of Maritime Villeggiatura. Such practice exists so that people settle temporarily on the beach as a second home, interfering in the Regulation of the land use as well as in the urban planning of Tibau, promoting urbanization based in the logic of leisure, with enormous capacity for appropriation and space consumption. The practice of Maritime Villeggiatura in Tibau began in the late nineteenth century, becoming more relevant in the 1980s, when the practice became fashionable for the citizens of Mossoró City, in view of their economic strength, and consumption power to invest in this type of domicile. Tibau has become a great depository of second homes for leisure practice, which contributed even to the city administrative and political emancipation in 1997. The intensification of Real Estate activities, expanding second homes along the coast, results in the urbanization of Tibau territory with the assistance of Local Government, whom was interested in entering Tibau on the State tourism routes. The used methodology comprised literature review, data collection and local observation. Questionnaires were applied in the form of interviews to the villeggiaturistas, local residents, business and trade services local companies, a local agricultural firm named Agricultura Famosa Ltda., Municipal government and the Association of Senior Citizens of the municipality of Tibau. A photographic record was made to visualize the urbanization evolution of Tibau. It has also been taken georeference measures of the area object of study in this research, in order to analyze the use and occupation of the territory by urban and social agents villeggiaturistas and residents. The conclusion is that the urbanization process that has been taken in Tibau occurred along the coast shore, with low population density, and therefore creating difficulties to governance of the Municipal government. Real Estate Sector has been promoting the value increase of urban land in order to fragment the space with private condominiums segregating local resident population to outlying areas of the city, away from the coastline and lacking infrastructure and basic urban services